Dispensasi Perkawinan Anak Setelah Adanya Perma Nomor 5 Tahun 2019 - Allika Fadia Tasya; Atik Winanti (Wajah Hukum, 2021)
Ratification of Law Number 16 of 2019 which regulates increasing the minimum age of a person to get married is an attempt to prevent child marriage. Because child marriage is a violation of children’s right. However child marriage still often happen in Indonesia and still many parents who apply marriage dispensation with an urgent reason. But in the practice, there is no specific regulation about this marriage dispensation there is no equality in adjudicating dispensation of marriage. This article use normative judicial research metodhs and use statute approach. The purpose of this research is to find answers about how the impact of child marriage on children’s right and analyze about judge’s consideration in adjudicating child marriage dispensation after there is Supreme Court Regulation Number 5 of 2019. Based on the results of this research were found that child marriage make children difficult to get their rights. Because they have new responsibility to take care of their marriage life. Eventhough there was a regulation that regulate about child’s right but it’s implementation not maximal yet, especially for who married in the child age. Then now regulation about marriage dispensation has been specially regulated in Supreme Court Regulation Number 5 of 2019 about guidelines for adjudicating applications for marriage dispensation that can used for every judge in the court which prioritize the best interests of child principle.